ABOUT THE FRENCH TRANSLATION OF NAVOI’S GAZELLE “BIZGA UL MAHVASH TILIYU KONGLI BIRLA YOR EMAS” (On the example of Navoi’s gazelles translated into French by Hamid Ismailov and Jean-Pierre Balp) - Matkarimov Saparboy Rajabovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2021)
In the article, the speech goes on about the translation of Navoi’s gazelle “Bizga ul mahvash tiliyu kongli birla yor emas” into Freench language by Hamid Ismailov and Jean-Pierre Balp. The author studied Uzbek scientists’ works on the issue and thoroughly analyzed the translation of the gazelle and its original form.